Estimation of Effective Dose from the Atmospheric Nuclear Tests Due to the Intake of Marine Products - NAKANO, Masanao (Hoken butsuri, 2007)
The worldwide environmental protection is required by the public. A long-term environmental assessment from nuclear fuel cycle facilities to the aquatic environment also becomes more important to understand longterm risk of nuclear energy. Evaluation of long-term risk including not only in Japan but also in neighboring countries is considered to be necessary in order to develop sustainable nuclear power industry. The author successfully simulated the distribution of radionuclides in seawater and seabed sediment produced by atmospheric nuclear tests using LAMER (Long-term Assessment ModEl of Radionuclides in the oceans). A part of the LAMER calculated the advection-diffusion-scavenging processes for radionuclides in the oceans and the Japan Sea in cooperate with Oceanic General Circulation Model (OGCM) and was validated. The author is challenging to calculate probabilistic effective dose suggested by ICRP from intake of marine products due to atmospheric nuclear tests using the Monte Carlo method in the other part of LAMER. Depending on the deviation of each parameter, the 95th percentile of the probabilistic effective dose was from one third to two thirds of the 95th percentile of the deterministic effective dose in proforma calculation. It means that probabilistic assessment can contribute to the design and optimisation of a nuclear fuel cycle facility.